The Application of Short Interval Training Method Based on High Maximum Aerobic Speed Capacity to Improve Aerobic Capacity - Sindy Fitri Yunita; Dikdik Zafar Sidik; Fitri Rosdiana; Sendi Cornelia (Journal of Physical Education Health and Sport, 2025)
Aerobic capacity is a crucial component of an athlete’s performance, especially in team sports like futsal, which require high endurance. Short Interval Training (SIT) has been widely used to improve aerobic capacity; however, individualized approaches based on Maximum Aerobic Speed (MAS) remain limited. This study aims to investigate the effect of a SIT program based on high MAS on the aerobic capacity among female futsal athletes. An experimental method with a one-group pretest–posttest design was used, involving five athletes from the Student Activity Unit at Universitas Pendidikan Indonesia. Participants underwent 16 training sessions over 8 weeks, with intensities set at ≥95% of each athlete’s maximal effort. VO₂max was measured before and after the training program. Statistical analysis using a paired sample t-test showed a significant improvement in VO₂max from 39.39 to 40.73 ml/kg/min (p = 0.004, p < 0.05). This approach allows for better training precision and physiological adaptation by adjusting workloads according to each athlete’s aerobic threshold. These findings indicate that SIT program based on high MAS is effective in improving aerobic capacity and enhancing recovery during the match. The results support the implementation of SIT program based on high MAS as an efficient and personalized training strategy for athlete conditioning programs.